2018
DOI: 10.1016/j.econmod.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of sovereign debt in China: Sustainability and structural change

Abstract: The dynamics of public debt are an important determinant of the macroeconomic environment of an economy and of the investment climate in the private sector. There have been concerns recently about the sustainability of debt in China, given the surge in the fiscal deficit in the last few years that has aided economic activity. This paper aims to shine some light on the dynamics of public debt in the Chinese economy given the risk of a debt crisis, taking nonlinearities and structural breaks into account. Our re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Fiscal sustainability in Asia is also assessed using country-specific time series, for instance Japan (Doi et al, 2011;Sakuragawa and Hosono, 2011), China (Cuestas and Regis, 2018), India (Pradhan, 2014) and Vietnam (Hoai et al, 2015). For the Japanese case, all the studies conclude that fiscal policy is unsustainable.…”
Section: Empirical Results For Asian Countriesmentioning
confidence: 99%
“…Fiscal sustainability in Asia is also assessed using country-specific time series, for instance Japan (Doi et al, 2011;Sakuragawa and Hosono, 2011), China (Cuestas and Regis, 2018), India (Pradhan, 2014) and Vietnam (Hoai et al, 2015). For the Japanese case, all the studies conclude that fiscal policy is unsustainable.…”
Section: Empirical Results For Asian Countriesmentioning
confidence: 99%
“…Subsequently, the Chinese government has adopted the expansion of its fiscal policies. Cuestas and Regis (2018) have tried to analyze time series properties of public debt of China. The findings of the study revealed that Chinese debt accumulation is non-stationary.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The previous studies examine the level of debt sustainability and the factors that determine it, such as debt dynamic in Pakistan (Chandia, & Javid, 2013), fiscal limit and external debt risk (Bi, Shen & Yang, 2014), debt dynamic in China (Cuestas & Regis, 2017), debt sustainability and non-linear primary balance (Fournier & Fall, 2017), debt sustainability and fiscal reaction functions in India (Kaur, Mukherjee & Ekka, 2017), macroeconomic dynamic and external debt (Semmler & Tahri, 2017), long-run debt and structural primary balance (Beqiraj, Fedeli & Forte, 2018), monetary policy and debt equilibrium (Cavalcanti, et al, 2018), external debt and economic growth (Edo, Osadolor & Dading, 2019). Conceptually, Semmler & Tahri (2017) suggest that debt dynamic analysis to assess external debt sustainability should be done using a non-linear approach and dynamic macroeconomic models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another condition will occur when the increased risk of external debt is triggered by exchange rate volatility and the fiscal limit decreases over time (Bi, Shen & Yang, 2014). Macroeconomic instability and an unreliable fiscal policy can also encourage debt accumulation to become unsustainable (Cuestas & Regis, 2017). The higher debt accumulation and the indication of a decrease in the interest rate will be responded significantly by the primary balance to GDP ratio under the debt limit approach (Fournier & Fall, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%